Public Value Motivations for Debt Issuance in America's Cities. (30th November 2022) - Nukpezah, Julius A.; Dzigbede, Komla D.; Boadu, Bernard
Abstract: Although contemporary public administration and management scholarship has given much attention to public values that inform public decisions, research on the public values that motivate debt issuance is scant. However, understanding the public values that motivate local governments' debt issuance can contribute to excellence in public service delivery, impact governance, and enhance citizen participation in government as well as public managers' overall behavior. The present article examines public values that motivate debt issuance by using case studies of seven large U.S. cities over a 4-year period (2016–2019). It employs an interpretivist rather than a positivist approach in the empirical investigations. The findings reveal that debt issuance in U.S. cities is motivated by a range of public values that reflect expected public outcomes related to community resilience, local productivity, and human development. Local public managers must consider contemporary public values when making critical decisions about long-term debt issuance, given the importance of such decisions for the sustainability of U.S. cities.